Analysis of the Safety and Pregnancy Outcomes of Fertility-sparing Surgery in Ovarian Malignant Sex Cord-stromal Tumours: A Multicentre Retrospective Study. Issue 2 (February 2023) - Li, J.; Chu, R.; Wang, Z.; Chen, G.; Shen, Y.; Lou, Y.; Li, L.; Sun, C.; Li, K.; Song, L.; Qin, T.; Li, J.; et al.
Abstract: Aims: To assess the difference in survival between fertility-sparing surgery (FSS) and radical surgery and explore pregnancy outcomes after FSS in stage I malignant sex cord-stromal tumours (MSCSTs). Materials and methods: We carried out a multicentre retrospective cohort study on patients who were diagnosed with MSCSTs and the tumour was confined to one ovary. The patients were divided into FSS and radical surgery groups. Inverse probability of treatment weighting (IPTW) was used to balance variables between the two groups. Kaplan–Meier analysis was used to compare the difference in disease-free survival (DFS). Univariate and multivariate Cox regression analysis was used to find risk factors of DFS. Univariate logistic regression analysis was used to assess risk factors of pregnancy. Results: In total, 107 patients were included, of whom 54 (50.5%) women underwent FSS and 53 (49.5%) received radical surgery. After IPTW, a pseudo-population of 208 was determined and all of the covariates were well balanced. After a median follow-up time of 50 months (range 7–156 months), 10 patients experienced recurrence and two died. There was no significant difference in DFS between the two groups, both in unweighted ( P = 0.969) or weighted cohorts ( P = 0.792). In the weighted cohort, stage IC ( P = 0.014), tumour diameter >8 cm ( P = 0.003), incomplete staging surgery ( P = 0.003) and no adjuvant chemotherapy ( P < 0.001) were the four high-risk factors associated with a shorter DFS. Among 14 patients who had pregnancy desire, 11 (78.6%) women conceived successfully; the live birth rate was 76.9%. In univariate analysis, only adjuvant chemotherapy ( P = 0.009) was associated with infertility. Conclusions: On the premise of complete staging surgery, FSS is safe and feasible in early stage MSCSTs with satisfactory reproductive outcomes. Highlights: The first multicentre retrospective assessment of fertility-sparing surgery on malignant sex cord-stromal tumours. Fertility-sparing surgery had no adverse effect on disease-free survival in early stage malignant sex cord-stromal tumours. Complete staging surgery and adjuvant chemotherapy could significantly prolong disease-free survival. Patients had favourable pregnancy outcomes after fertility-sparing surgery.